Electrochemical Reduction of α‐Amino Allenylphosphonates to α‐Amino Allylphosphonates. Issue 25 (20th May 2020) - Adler, Pauline; de Oliveira, Pedro; Rabasso, Nicolas
Abstract : α‐Amino allenylphosphonates are reduced to α‐amino allylphosphonates using electrochemical processes. The reduction products are obtained in moderate to good yields. Moreover, in the case of tosylamine compounds, we were pleased to take advantage of a simultaneous reduction and cleavage of the tosyl group from the nitrogen atom to access unprotected amino‐allylphosphonates. The mechanism of this reduction is also discussed. Abstract : Table of content text: The selective reduction of allenyl to allylphosphonates was achieved using an efficient electrochemical method. The reduction products are obtained in moderate to good yields. Moreover, in the case of tosylamine compounds, the unprotected amino‐allylphosphonates were accessed through a simultaneous reduction and cleavage of the tosyl group from the nitrogen atom. The mechanism of this reduction is also discussed.